2018
DOI: 10.1038/s41395-018-0211-8
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Infections Are Common in Patients with Flares of Inflammatory Bowel Disease

Abstract: Non-Clostridium difficile enteric infections were identified in 17% of symptomatic patients with IBD. Endoscopic and histologic findings may not differentiate flare from infection. Norovirus and E.coli may play an important role in flare of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 38 publications
4
53
1
Order By: Relevance
“…This allows for the primimg of colitogenic CD8 + T cells at the gut barrier site, resulting in microbiota-dependent activation of CD8 + T cells and colitis. In line with these results, Norovirus infection has been associated with exacerbations and flares of IBD 49,50 . Our data would suggest that these flares are the result of a transient reduction in Treg cells that is compensated by the expansion and conversion of Vβ2 + T cells into Treg cells as observed in the IBD pateints with inactive disease.…”
Section: Discussionsupporting
confidence: 71%
“…This allows for the primimg of colitogenic CD8 + T cells at the gut barrier site, resulting in microbiota-dependent activation of CD8 + T cells and colitis. In line with these results, Norovirus infection has been associated with exacerbations and flares of IBD 49,50 . Our data would suggest that these flares are the result of a transient reduction in Treg cells that is compensated by the expansion and conversion of Vβ2 + T cells into Treg cells as observed in the IBD pateints with inactive disease.…”
Section: Discussionsupporting
confidence: 71%
“…In contrast, in a recent study from Mayo Clinic using conventional stool testing in IBD patients presenting with flare, rate of non-CDI bacterial infections was very low (< 3%) and did not influence disease course over 1 year, as compared to IBD patients who tested negative for infection or in patients with CDI; similar to this study, conventional stool testing in our study did not identify a single non-CDI pathogen [6]. Furthermore, a recent study from Columbia University Medical Center using GPP testing in IBD patients presenting with flare showed that GPPpositive patients treated with antibiotics for non-CDI had no difference in outcomes at median follow-up of 10.5 months compared to untreated GPP-positive patients for non-CDI [11]. While further studies assessing outcomes for non-CDI in IBD patients are needed, currently a C. difficile toxin PCR only diagnostic strategy and/or increasing scrutiny prior to prescribing antibiotics for a positive GPP test is warranted.…”
supporting
confidence: 80%
“…Cross‐sectional studies demonstrate unique microbial signatures and T‐cell populations for IBD subtypes 6,7 . GI infection is a common cause of gut dysbiosis, and several studies have reported an association among enteric infection, functionally altered commensal bacteria, and IBD 5,8,9 . By contrast, some microbes, such as Helicobacter pylori and helminths, are inversely associated with IBD, particularly CD.…”
Section: Introductionmentioning
confidence: 99%